Dekadenz und Klassik: Dmitri Mereschkowskis Übersetzungen der griechischen Tragödien - Uspenskaja, Anna (Hyperboreus, 2016)
The article deals with translations of ancient Greek tragedies by D. S. Merezhkovskij, one of the founders and most important representatives of Russian symbolism. Translating Aeschylus, Sophocles, and Euripides, he aimed at reviving Greek theater in Russia and thought it would be a means of reviving modern art in general.Going back to Classical Antiquity as a source of new forms and ideas was of great religious and philosophical importance for Merezhkovskij. He considered Oedipus, Antigone, and Hippolytus great symbols of chastity and innocence, preceding Christ but essentially Christian. Thus the idea of decadence, universal decline, and the ruin of culture combined in his creative mind with the classicist belief in ancient theater as a permanent ideal that can still prevent culture from total destruction. This conviction led him to produce masterpieces of ancient drama in his translation in Alexandrinsky Theater in St Petersburg.